2020
DOI: 10.1111/ppl.13254
|View full text |Cite
|
Sign up to set email alerts
|

Esca‐affected grapevine leaf metabolome is clone‐ and vintage‐dependent

Abstract: Esca is a complex grapevine trunk disease caused by wood‐rotting ascomycetes and basidiomycetes and leading to several foliar and wood symptoms. Given that the esca expression can be influenced by several environmental, physiological, and genetic factors, foliar symptoms are inconsistent in incidence and prevalence and may appear 1 year but not the following. We have previously reported a clone‐dependent expression of the disease in cv Chardonnay. Owing to metabolome analysis, we could discriminate the metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Thus, the effective water received by the plant seemed to have played a major role in symptom development in our study; this is supported by the PCA analysis, which showed that, out of all the meteorological variables, effective water had the highest correlation with symptom occurrence (Tables 2S to 5S, Figure 1S). Similar yeardependent GTD foliar symptom expression is reported in the literature (Mugnai et al, 1999;Fischer and Peighami-Ashnaei, 2019;Moret et al, 2020). In general, drought has been frequently considered as a pre-disposing factor for woody plant declines in forest trees (Desprez-Loustau et al, 2006;Piou et al, 2006) and grapevine (Surico et al, 2006;Claverie et al, 2020), because the reduced water availability limits photosynthesis and thus the carbon allocation useful for growth and defence response.…”
Section: A Vintage-dependent Effect On Foliar Symptom Expression Rela...supporting
confidence: 58%
“…Thus, the effective water received by the plant seemed to have played a major role in symptom development in our study; this is supported by the PCA analysis, which showed that, out of all the meteorological variables, effective water had the highest correlation with symptom occurrence (Tables 2S to 5S, Figure 1S). Similar yeardependent GTD foliar symptom expression is reported in the literature (Mugnai et al, 1999;Fischer and Peighami-Ashnaei, 2019;Moret et al, 2020). In general, drought has been frequently considered as a pre-disposing factor for woody plant declines in forest trees (Desprez-Loustau et al, 2006;Piou et al, 2006) and grapevine (Surico et al, 2006;Claverie et al, 2020), because the reduced water availability limits photosynthesis and thus the carbon allocation useful for growth and defence response.…”
Section: A Vintage-dependent Effect On Foliar Symptom Expression Rela...supporting
confidence: 58%
“…Nevertheless, because a Fmed-Pch-Pmin interaction has been demonstrated, a relationship is likely between those compounds and Fmed (Sparapano et al, 2001b;Bruez et al, 2020). For this reason, results from most metabolomic studies in leaves responding to "Esca disease"-associated pathogens should be treated with caution, when attempting to understand exact plant responses to Fmed (Goufo et al, 2019;Moret et al, 2021). Further studies are necessary to precisely determine grapevine metabolite production burst specifically in response to Fmed colonization.…”
Section: Host Physiology Changes and Defense Responses Following F Mediterranea Infectionsmentioning
confidence: 99%
“…ii) No completely resistant grape cultivar has been reported, but cultivar and clone contributions to symptom expression and severity have been observed and reviewed (Marchi, 2001;Quaglia et al, 2009;Murolo and Romanazzi, 2014;Kraus et al, 2019;Moret et al, 2019;Songy et al, 2019a;Moret et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Yield loss can be as much as 20%. Leaf metabolite fingerprints have been performed on two different clones of Trousseau, an esca‐susceptible cultivar (Moret et al, 2021). A clone‐ and year‐dependent metabolic response is demonstrated.…”
Section: Pathogensmentioning
confidence: 99%